2002
DOI: 10.3171/foc.2002.12.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Atlantal lateral mass screws for posterior spinal reconstruction

Abstract: Object A variety of techniques may be used to achieve fixation of the upper cervical spine. Transarticular atlantoaxial screws, posterior interspinous cable and graft constructs, and interlaminar clamps have been used effectively to achieve atlantoaxial fixation. Various anatomical factors, however, may preclude the successful application of these techniques. These factors include aberrant vertebral artery anatomy, irreducible atlantoaxial subluxation, exaggerated ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 17 publications
1
44
0
Order By: Relevance
“…55 The purported benefits include longer bony purchase, increased rigidity, less C2 ganglion manipulation and postoperative neuralgia, and less intraoperative blood loss due to less disruption of the perineural venous plexus. 9,11,56 The broad posterior arch of the atlas is the best location for this modified screw placement. Although this may be reasonable for most patients, in patients with a PP, the anomaly has the possibility of being misidentified as the broad posterior arch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…55 The purported benefits include longer bony purchase, increased rigidity, less C2 ganglion manipulation and postoperative neuralgia, and less intraoperative blood loss due to less disruption of the perineural venous plexus. 9,11,56 The broad posterior arch of the atlas is the best location for this modified screw placement. Although this may be reasonable for most patients, in patients with a PP, the anomaly has the possibility of being misidentified as the broad posterior arch.…”
Section: Discussionmentioning
confidence: 99%
“…7 Since the treatment of atlantoaxial instability was revolutionized by the introduction of the C1LMS insertion, 8 many alterations to the method have been described and used successfully. [9][10][11] Young et al 4 reported that mistaking the PP for just a broad posterior arch of the atlas during C1LMS placement could cause injury to the vertebral artery.…”
Section: Introductionmentioning
confidence: 99%
“…Atlanto-axial instability from trauma, tumour, inflammation, or congenital defect as well as painful osteoarthritis are recognised indications for atlanto-axial fusion [3,9,14,20]. The posterior approach is by far the most common approach for C1-C2 fixation and dorsal wiring techniques have increasingly been replaced by newer screw fixation techniques [3,9,10,12,14,15,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…The posterior approach is by far the most common approach for C1-C2 fixation and dorsal wiring techniques have increasingly been replaced by newer screw fixation techniques [3,9,10,12,14,15,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…This highlights theIntroduction C1 lateral mass screw fixation was first described in 1994 by Goel and Laheri [3] and popularized by Harms and Melcher in 2001 [6]. The advantages of this technique over the Magerl transarticular screw technique include the intraoperative ability to reduce C1/2 subluxation and a theoretical reduction in the risk of vertebral artery injury [1,2]. While occipital neuralgia has been recognized as a possible complication of C1 lateral mass fixation, there have been few documented reports to date.…”
mentioning
confidence: 97%